Development and evaluation of e-comic nervous system app to enhance self-directed student learning - Hendra Susanto; Deny Setiawan; Susriyati Mahanal; Zahra Firdaus; Claresia Tsany Kusmayadi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Technological developments in various fields are the key to progress in the digital era. The utilization of technology-based learning media in education makes learning more interactive and supports independent learning. This study aims to develop and test the practicality and effectiveness of storyline-based nervous system e-comics media to support students' independent learning. This research uses the Research and Development (RnD) method with the Lee & Owen model, consisting of the analysis, design, development, implementation, and evaluation stages. The research was conducted with the subjects in this study, class XI MIPA SMA Negeri 2 Malang students, totalling 60 people. A pre-experimental design of one group pretest-posttest was used to test the effectiveness of the media. Data were collected through questionnaires and tests. The media validation results obtained 100%, material validation 100%, and student response results 98.7% in the class trial. The effectiveness test used a Pretest-Posttest Control Group Design. The results showed a significant difference between the posttest of both classes with Sig. (2-tailed) 0.00 <0.05, there is a significant difference between the control and experimental classes. Storyline-based nerve e-comic media can facilitate independent learning more interestingly and interactively.